2017
DOI: 10.3390/nano7110361
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric Nanoparticles in Liquid Crystals: Recent Progress and Current Challenges

Abstract: The dispersion of ferroelectric nanomaterials in liquid crystals has recently emerged as a promising way for the design of advanced and tunable electro-optical materials. The goal of this paper is a broad overview of the current technology, basic physical properties, and applications of ferroelectric nanoparticle/liquid crystal colloids. By compiling a great variety of experimental data and discussing it in the framework of existing theoretical models, both scientific and technological challenges of this rapid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(31 citation statements)
references
References 122 publications
(405 reference statements)
0
31
0
Order By: Relevance
“…The reasons for the different behaviour observed may be the uncontrollable ionic contamination, broad size distribution and irregular shapes of particles, poor dispersibility, etc. For example, it has been reported that large ferroelectric particles (>100 nm) can form a polydomain structure but very small particles (<10 nm) may lose their ferroelectricity [98].…”
Section: Modification Of Physical Properties Of Lc Materials By Nanodmentioning
confidence: 99%
See 1 more Smart Citation
“…The reasons for the different behaviour observed may be the uncontrollable ionic contamination, broad size distribution and irregular shapes of particles, poor dispersibility, etc. For example, it has been reported that large ferroelectric particles (>100 nm) can form a polydomain structure but very small particles (<10 nm) may lose their ferroelectricity [98].…”
Section: Modification Of Physical Properties Of Lc Materials By Nanodmentioning
confidence: 99%
“…For example, there are abundant reports declaring that doping metallic, semiconducting, oxide and ferroelectric nanoparticles into LCs can efficiently modify the electrical and mechanical (viscoelastic) properties of LC host, leading to large dielectric and optical anisotropy, low threshold voltage, and an improved electro-optical response [87,92,94,96,97]. In addition, ferroelectric nanoparticles can also increase the order parameter as well as the clearing point of the LC host due to the interaction between the elastic forces of LC molecules and the spontaneous polarization of ferroelectric nanoparticles [86,[98][99][100][101]. Doping nematic LCs with ferromagnetic particles can effectively reorient the director of LCs by magnetic fields induced by the coupling of magnetic particles with LC molecules [83,[102][103][104][105][106].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, liquid crystals doped with nano-objects have emerged as novel tunable materials with advanced functionalities [41][42][43][44][45][46][47]. Electrical properties of liquid crystals doped with ferroelectric [48][49][50][51][52][53][54], magnetic [55][56][57], metal [58][59][60][61][62][63], semiconductor and dielectric [64][65][66][67][68][69], and carbon-based (fullerenes, carbon nanotubes, graphene, diamond) nanomaterials [70][71][72][73][74][75] were studied by many research teams (see also recent reviews [76,77] and references therein). The ion capturing effect is naturally expected for nanomaterials dispersed in liquid crystals.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of LC on modern technology such as a biosensor, memory devices, LC-based lasers, holography has been profound [8,9]. Besides these modern familiar applications, there are other devices with improved properties of LC by doping nanoparticles or mixing with other inorganic/organic solvents as LCs are favorable material for the effective transfer of ions and electrons [6,[10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%